Computational modeling reveals key molecular properties and dynamic behavior of disruptor of telomeric silencing 1‐like (DOT1L) and partnering complexes involved in leukemogenesis. Issue 1 (12th September 2021) - Stodola, Timothy J.; Chi, Young‐In; De Assuncao, Thiago M.; Leverence, Elise N.; Tripathi, Swarnendu; Dsouza, Nikita R.; Mathison, Angela J.; Volkman, Brian F.; Smith, Brian C.; Lomberk, Gwen; Zimmermann, Michael T.; Urrutia, Raul
Abstract: Disruptor of telomeric silencing 1‐like ( DOT1L ) is the only non‐SET domain histone lysine methyltransferase (KMT) and writer of H3K79 methylation on nucleosomes marked by H2B ubiquitination. DOT1L has elicited significant attention because of its interaction or fusion with members of the AF protein family in blood cell biology and leukemogenic transformation. Here, our goal was to extend previous structural information by performing a robust molecular dynamic study of DOT1L and its leukemogenic partners combined with mutational analysis. We show that statically and dynamically, D161, G163, E186, and F223 make frequent time‐dependent interactions with SAM, while additional residues T139, K187, and N241 interact with SAM only under dynamics. Dynamics models reveal DOT1L, SAM, and H4 moving as one and show that more than twice the number of DOT1L residues interacts with these partners, relative to the static structure. Mutational analyses indicate that six of these residues are intolerant to substitution. We describe the dynamic behavior of DOT1L interacting with AF10 and AF9. Studies on the dynamics of a heterotrimeric complex of DOT1L1‐AF10 illuminated describe coordinated motions that impact the relative position of the DOT1L HMT domain to the nucleosome. The molecular motions of the DOT1L–AF9 complex are less extensive and highly dynamic, resembling a swivel‐like mechanics. Through molecular dynamics and mutational analysis, we extend the knowledge previous provided by static measurements. These results are important to consider when describing the biochemical properties of DOT1L, under normal and in disease conditions, as well as for the development of novel therapeutic agents.